The Worldwide Depression, 1929-1939 - Rothermund, Dietmar (Brill | Manohar Publishers & Distributors, 2016)
The Great Depression affected the whole world, but most studies of this crucial phenomenon have only dealt with the industrialized countries and have neglected the peasants of Asia, Africa and Latin America. The present study adopts a global point of view and covers the fate of the peasantry at the periphery of the world market in addition to that of the nations of Europe and North America. It also deals with the political consequences of the economic decline and its aftermath. The tragedy of the international gold standard, the problems of agricultural production and the recoil of global credit are discussed in detail. The experiences of all major countries have been outlined in specific chapters. Recent research work has been summarized and the blind spots of earlier economic analyses have been highlighted. A comprehensive annotated bibliography is added to the text. This volume is invaluable for the scholar of Modern Economic History.